2021
DOI: 10.1002/lno.11716
|View full text |Cite
|
Sign up to set email alerts
|

How hydrology and anthropogenic activity influence the molecular composition and export of dissolved organic matter: Observations along a large river continuum

Abstract: Large rivers are the main arteries for transportation of carbon to the ocean; yet, how hydrology and anthropogenic disturbances may change the composition and export of dissolved organic matter along large river continuums is largely unknown. The Yangtze River has a watershed area of 1.80 × 10 6 km 2 . It originates from the Qinghai-Tibet Plateau and flows 6300 km eastward through the center of China. We collected samples (n = 271) along the river continuum and analyzed weekly samples at the most downstream si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…These sites were either positioned in shallow environments near islands or in the effluent of WWTPs. Streams affected by inputs of human sewage have been shown to possess a contrasting DOM composition characterized in part by higher proportions of highly labile microbial OM and low aromatic content (Petrone et al 2009; Williams et al 2016; Khamis et al 2018; Zhou et al 2021). Therefore, disproportionate inputs of protein‐rich DOM in areas with high influence of human activity could partly explain the high peaks in the concentrations of BDOC, but our data suggest that these inputs must also be coupled to specific environmental conditions (i.e., nutrients Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These sites were either positioned in shallow environments near islands or in the effluent of WWTPs. Streams affected by inputs of human sewage have been shown to possess a contrasting DOM composition characterized in part by higher proportions of highly labile microbial OM and low aromatic content (Petrone et al 2009; Williams et al 2016; Khamis et al 2018; Zhou et al 2021). Therefore, disproportionate inputs of protein‐rich DOM in areas with high influence of human activity could partly explain the high peaks in the concentrations of BDOC, but our data suggest that these inputs must also be coupled to specific environmental conditions (i.e., nutrients Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, C1 and C2 were identified as terrigenous components, with C1 being most closely correlated to agricultural activities; C3 was identified as an endogenous component. Previous studies have indicated that increasing intensities of agricultural activities around lakes leads to increased input of terrigenous humus-like substances [ 44 , 45 ]. This was reflected in Baoan Lake and Daye Lake, which are surrounded by widely distributed agricultural areas, and whose total proportions of component C1 in the FDOM of sediments were 47.82% and 47.41%, respectively ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Especially, a significant loss of aquatic habitats has occurred in most watersheds because of agricultural activities, urbanization, and dam constructions (Bao et al, 2015;Wagner et al, 2015;Riedel et al, 2016;Li et al, 2018a). Understanding the biogeochemical transformation of DOM across the fluvial networks will ultimately help predicting how anthropogenic influences may be altering DOM composition and turnover (Battin et al, 2008;Bao et al, 2015;Riedel et al, 2016;He et al, 2020;Zhou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Koch et al, 2005;Hertkon et al, 2006;Kellerman et al, 2014;Wagner et al, 2015;Riedel et al, 2016;Bahureksa et al, 2021). Chemical signatures in large rivers mirror various DOM sources and transformations, such as photo-and microbial degradation, geomorphological and hydrological processes (Roth et al, 2013;Seidel et al, 2015;Wagner et al, 2015;Riedel et al, 2016;He et al, 2020;Zhou et al, 2021). An increasing number of studies emphasizes the role of human actives on the composition of riverine DOM.…”
Section: Introductionmentioning
confidence: 99%